2012
DOI: 10.1007/s00420-012-0763-7
|View full text |Cite
|
Sign up to set email alerts
|

Physical job demands and related health complaints among surgeons

Abstract: PurposeSurgeons’ poor physical health and high physical job demands might threaten good quality of care. We aimed to compare the prevalence of physical complaints of surgeons, their physical work ability and the physical job demands of surgeons with that of other hospital physicians.MethodsAll medical doctors (n = 958) of one academic medical center were invited to complete the online questionnaire to assess the physical work ability and the prevalence of regional musculoskeletal complaints. A purposive sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 21 publications
3
39
0
3
Order By: Relevance
“…Another kind of pain and discomfort described by the authors were leg edema and varicose veins (20%). In comparison with clinical physicians at the hospital studied by Ruitenburg, Frings-Dresen and Sluiter (2013), surgeons made fine repetitive movements 26 times longer and stood up 130% longer. Moreover, 73% of the surgeons felt troubled about working in uncomfortable and exhaustive postures.…”
Section: Physical Healthmentioning
confidence: 94%
See 1 more Smart Citation
“…Another kind of pain and discomfort described by the authors were leg edema and varicose veins (20%). In comparison with clinical physicians at the hospital studied by Ruitenburg, Frings-Dresen and Sluiter (2013), surgeons made fine repetitive movements 26 times longer and stood up 130% longer. Moreover, 73% of the surgeons felt troubled about working in uncomfortable and exhaustive postures.…”
Section: Physical Healthmentioning
confidence: 94%
“…The majority (83.3%) comprised cross-sectional studies. Within this type of methodology, the main issues addressed in the studies on physical health were musculoskeletal disorders (AUeRBACH et al, 2011;MeHRDAD;DeNNeRLeiN;MORDHeSiZADeH, 2012;RUiTeNBURG;FRiNGS-DReSeN;SLUiTeR, 2013;MOHSeNi-BANDPei et al, 2011;LiANG et al, 2013) and ophthalmologic health (MReNA et al, 2011;KRUPiNSKi;BeRBAUM, 2009 Rauchenzauner et al (2009) found that frequent stressing situations, sleep deficit, and deregulation of the circadian rhythm are causes of the incidence of cardiovascular diseases in this group of professionals. Before the manifestation of symptoms of cardiovascular diseases, after night shifts physicians presented an increase in the cardiac frequency, as well as the elevation of blood pressure, dysrhythmia, altered catecholamine secretion, and an increase of serum cholesterol, uric acid, and potassium.…”
Section: Physical Healthmentioning
confidence: 99%
“…, Ruitenburg et al . ). Working in uncomfortable or awkward positions for prolonged periods can also affect surgeons' performance (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…For example, they have to adopt and maintain working postures that are perceived as uncomfortable and exhausting [1,2], are confronted with high emotional peak demands [3], and work long hours with little job control [4,5]. Common adverse health effects associated with these job demands include neck, lower back and arm complaints [2,6,7].…”
Section: Introductionmentioning
confidence: 99%